2009
DOI: 10.20452/pamw.658
|View full text |Cite
|
Sign up to set email alerts
|

SNP rs198389 (T‑381 C) polymorphism in the B‑type natriuretic peptide gene promoter in patients with atherosclerotic renovascular hypertension

Abstract: SNP rs198389 (T-381 C) polymorphism in the B-type natriuretic peptide… 219 INTROduCTION Renovascular hypertension caused by renal artery stenosis (RAS) accounts for 3-5% of all cases of hypertension. It is considered that RAS can lead to glomerular ischemia and secondary blood pressure rise resulting from the renin-angiotensin-aldosterone system activation. Disturbed auto regulatory mechanisms may also play a key role in the development of hypertension because of the renal blood flow reduction and the increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…A study by Zhang et al [ 8 ] showed that the BNP gene SNP loci rs198389 and rs198388 are associated with the genetic susceptibility to congenital heart disease. Poreba et al [ 9 ] showed that the SNP at the rs198389 site of the BNP gene is associated with the development of atherosclerotic lesions in the renal artery. In addition, Fox et al [ 10 ] studies showed that the rs198389, rs6668352, and rs198388 SNP sites of the BNP gene were associated with ventricular dysfunction (VnD) after primary coronary bypass surgery.…”
mentioning
confidence: 99%
“…A study by Zhang et al [ 8 ] showed that the BNP gene SNP loci rs198389 and rs198388 are associated with the genetic susceptibility to congenital heart disease. Poreba et al [ 9 ] showed that the SNP at the rs198389 site of the BNP gene is associated with the development of atherosclerotic lesions in the renal artery. In addition, Fox et al [ 10 ] studies showed that the rs198389, rs6668352, and rs198388 SNP sites of the BNP gene were associated with ventricular dysfunction (VnD) after primary coronary bypass surgery.…”
mentioning
confidence: 99%
“…BNP genetic variants have also been associated with a modest effect in Type 2 diabetes susceptibility [48] and renal artery stenosis in patients with atherosclerotic renovascular hypertension [49].…”
Section: Genetics Of Npsmentioning
confidence: 99%
“…In nondiabetic subjects, there is no such effect of HbA1c, and high BNP is a predictor of progression of albuminuria [8]. Another reason of the predictive effect of low BNP on diabetic nephropathy might also be associated with genetic variation of BNP, since a single nucleotide polymorphism of BNP may be related to a low BNP level and reduced renal artery stenosis [43]. On the other hand, HbA1c also had a significant effect on albuminuria ( • ▶ Table 2, 3), but did not show a significant effect on remission of diabetic nephropathy ( • ▶ Fig.…”
Section: Endocrine Carementioning
confidence: 99%